2007
DOI: 10.1590/s0100-879x2006005000129
|View full text |Cite
|
Sign up to set email alerts
|

Direct costs of asthma in Brazil: a comparison between controlled and uncontrolled asthmatic patients

Abstract: Asthma is a common chronic illness that imposes a heavy burden on all aspects of the patient's life, including personal and health care cost expenditures. To analyze the direct cost associated to uncontrolled asthma patients, a cross-sectional study was conducted to determine costs related to patients with uncontrolled and controlled asthma. Uncontrolled patient was defined by daytime symptoms more than twice a week or nocturnal symptoms during two consecutive nights or any limitations of activities, or need f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 19 publications
0
24
1
3
Order By: Relevance
“…A recent study has demonstrated that subjects with uncontrolled asthma use more health resources than do those with controlled asthma. (20) In the present study, school absenteeism was higher among the patients with uncontrolled or partially controlled asthma (36.3% and 46.7%, respectively) than among those with controlled asthma (16.2%); however, these values are lower than that found in the AIRLA survey, in which 58% of the children interviewed reported having missed school because of an asthma attack. (7) Asthma symptoms can affect activities of daily living, as well as contributing to school absenteeism.…”
Section: Discussioncontrasting
confidence: 73%
“…A recent study has demonstrated that subjects with uncontrolled asthma use more health resources than do those with controlled asthma. (20) In the present study, school absenteeism was higher among the patients with uncontrolled or partially controlled asthma (36.3% and 46.7%, respectively) than among those with controlled asthma (16.2%); however, these values are lower than that found in the AIRLA survey, in which 58% of the children interviewed reported having missed school because of an asthma attack. (7) Asthma symptoms can affect activities of daily living, as well as contributing to school absenteeism.…”
Section: Discussioncontrasting
confidence: 73%
“…In a study with 90 participants that compared the direct costs of treating patients with controlled and uncontrolled asthma (45 per group) in a Brazilian tertiary health care unit, the mean age was similar to the age of our population, but the average monthly family income was lower [15]. Thirty-one patients had mild asthma (34.4%), 41 had moderate asthma (45.5%), and 18 (20.0%) had severe asthma: compared with our population, a slightly higher proportion of patients had severe asthma and a slightly lower proportion had mild asthma in that unit.…”
Section: Resultsmentioning
confidence: 99%
“…Asthma is a highly prevalent chronic disease that affects individuals of all ages, representing an important cause of morbidity and, consequently, direct and indirect healthcare expenditures. [1][2][3][4][5] The southern region of Brazil, characterized by a humid subtropical climate with well-defined seasons, moderately cold winters and hot summers, 6 presents the highest prevalence of diagnosis for this condition, estimated at 5.3% of adults. 7 Among elementary school students, the prevalence of clinical symptoms has been estimated at 23.6%.…”
Section: Introductionmentioning
confidence: 99%